DNA Mismatch Repair Protein (MSH6) Correlated With the Responses of Atypical Pituitary Adenomas and Pituitary Carcinomas to Temozolomide: The National Cooperative Study by the Japan Society for Hypothalamic and Pituitary Tumors - Hirohata, Toshio; Asano, Kenichiro; Ogawa, Yoshikazu; Takano, Shingo; Amano, Kosaku; Isozaki, Osamu; Iwai, Yoshiyasu; Sakata, Kiyohiko; Fukuhara, Noriaki; Nishioka, Hiroshi; Yamada, Shozo; Fujio, Shingo; et al. (The journal of clinical endocrinology and metabolism, 2013)
Context:Temozolomide (TMZ) is an alkylating agent and was a first-line chemotherapeutic agent for malignant gliomas. Recently, TMZ has been documented to be effective against atypical pituitary adenomas (APAs) and pituitary carcinomas (PCs).Objective:The clinical and pathological characteristics of APAs and PCs treated with TMZ in Japan were surveyed and analyzed retrospectively.Design:Members of the Japan Society of Hypothalamic and Pituitary Tumors were surveyed regarding the clinical characteristics of APAs and PCs treated with TMZ. Stored tumor samples were gathered from the responders and were assessed by the immunohistochemistry of Ki-67, O6-methyl-guanine-DNA methyltransferase, p53, MSH6, and anterior pituitary hormones. Responses to TMZ treatment were defined as complete response (CR), partial response (PR), progressive disease (PD), and stable disease (SD) according to RECIST (Response Evaluation Criteria in Solid Tumors) version 2.0.Subjects:Three samples from 3 subjects with APA and 11 samples from 10 subjects with PC were available.Results:The 13 subjects had APAs and PCs consisting of 5 prolactin-producing tumors, 5 ACTH-producing tumors, and 3 null cell adenomas. The clinical response to TMZ treatment was as follows: 4 cases of CR and PR (31%), 2 cases of SD (15%), 6 cases of recurrence after CR and PR (46%), and 1 case of PD (8%). However, considerable subjects had recurrent disease after a response to TMZ. The immunohistochemical findings of Ki-67, O6-methyl-guanine-DNA methyltransferase, and p53 did not show any significant correlation with the efficacy of TMZ. However, the immunopositivity of MSH6 was positively correlated with TMZ response (P = .015, Fisher's exact test).Conclusions:This study showed that preserving MSH6 function was contributory to the effectiveness of TMZ in malignant pituitary neoplasms. It is necessary to survey more cases and evaluate multifactor analyses.